Safe Space, Dangerous Territory: Young People's Views on Preventing Radicalization through Education-Perspectives for Pre-Service Teacher Education - Saija Benjamin; Visajaani Salonen; Liam Gearon; Pia Koirikivi; Arniika Kuusisto (MDPI AG, 2021)
Initiatives for preventing radicalization and violent extremism through education (PVE-E) have become a feature of global educational policy and educational institutions across all phases, from early childhood to universities, also in Finland. If schools may be regarded as safe spaces here for identity and worldview construction and experiences of belonging, the specific subject matter of PVE-E is also dangerous territory. Not least because of PVE-E's focus on radicalization, but above all because of perceptions of schools being used as an adjunct of governmental counter-terrorism policy. We argue that understanding young people's views on issues related to radicalization and violent extremism is critical in order to develop ethical, sustainable, contextualized, and pedagogical approaches to prevent hostilities and foster peaceful co-existence. After providing some critical framing of the Finnish educational context in a broader international setting, we thus examine young people's views (n = 3617) in relation to the safe spaces through online survey data gathered as a part of our larger 4-year research project Growing up radical? The role of educational institutions in guiding young people's worldview construction. Specifically focused on Finland but with potentially wider international implications, more understanding about the topic of PVE-E is needed to inform teacher education and training, to which our empirical data makes some innovative contribution.